Biosynthetic gene cluster profiling predicts the positive association between antagonism and phylogeny in Bacillus - Xia, Liming; Miao, Youzhi; Cao, A’li; Liu, Yan; Liu, Zihao; Sun, Xinli; Xue, Yansheng; Xu, Zhihui; Xun, Weibing; Shen, Qirong; Zhang, Nan; Zhang, Ruifu (Nature communications, 2022)
Understanding the driving forces and intrinsic mechanisms of microbial competition is a fundamental question in microbial ecology. Despite the well-established negative correlation between exploitation competition and phylogenetic distance, the process of interference competition that is exemplified by antagonism remains controversial. Here, we studied the genus Bacillus , a commonly recognized producer of multifarious antibiotics, to explore the role of phylogenetic patterns of biosynthetic gene clusters (BGCs) in mediating the relationship between antagonism and phylogeny. Comparative genomic analysis revealed a positive association between BGC distance and phylogenetic distance. Antagonistic tests demonstrated that the inhibition phenotype positively correlated with both phylogenetic and predicted BGC distance, especially for antagonistic strains possessing abundant BGCs. Mutant-based verification showed that the antagonism was dependent on the BGCs that specifically harbored by the antagonistic strain. These findings highlight that BGC-phylogeny coherence regulates the positive correlation between congeneric antagonism and phylogenetic distance, which deepens our understanding of the driving force and intrinsic mechanism of microbial interactions. Interference competition exemplified by antagonism remains controversial. Using comparative genomic analysis and antagonistic assessments, this study shows that the distribution profile of biosynthetic gene clusters within Bacillus genomes is consistent with their phylogenetic relationship and that congeneric antagonism among Bacillus strains is positively correlated with phylogenetic distance.